BCG invokes superior STING‐mediated innate immune response over radiotherapy in a carcinogen murine model of urothelial cancer. Issue 2 (10th December 2021) - Lombardo, Kara A; Obradovic, Aleksandar; Singh, Alok Kumar; Liu, James L; Joice, Gregory; Kates, Max; Bishai, William; McConkey, David; Chaux, Alcides; Eich, Marie‐Lisa; Rezaei, M Katayoon; Netto, George J; et al.
Abstract: Radiation and bacillus Calmette–Guérin (BCG) instillations are used clinically for treatment of urothelial carcinoma, but the precise mechanisms by which they activate an immune response remain elusive. The role of the cGAS–STING pathway has been implicated in both BCG and radiation‐induced immune response; however, comparison of STING pathway molecules and the immune landscape following treatment in urothelial carcinoma has not been performed. We therefore comprehensively analyzed the local immune response in the bladder tumor microenvironment following radiotherapy and BCG instillations in a well‐established spontaneous murine model of urothelial carcinoma to provide insight into activation of STING‐mediated immune response. Mice were exposed to the oral carcinogen, BBN, for 12 weeks prior to treatment with a single 15 Gy dose of radiation or three intravesical instillations of BCG (1 × 10 8 CFU). At sacrifice, tumors were staged by a urologic pathologist and effects of therapy on the immune microenvironment were measured using the NanoString Myeloid Innate Immunity Panel and immunohistochemistry. Clinical relevance was established by measuring immune biomarker expression of cGAS and STING on a human tissue microarray consisting of BCG‐treated non‐muscle‐invasive urothelial carcinomas. BCG instillations in the murine model elevated STING and downstream STING‐induced interferon and pro‐inflammatory molecules, intratumoral M1 macrophage and T‐cell accumulation, and complete tumor eradication. In contrast, radiotherapy caused no changes in STING pathway or innate immune gene expression; rather, it induced M2 macrophage accumulation and elevated FoxP3 expression characteristic of immunosuppression. In human non‐muscle‐invasive bladder cancer, STING protein expression was elevated at baseline in patients who responded to BCG therapy and increased further after BCG therapy. Overall, these results show that STING pathway activation plays a key role in effective BCG‐induced immune response and strongly indicate that the effects of BCG on the bladder cancer immune microenvironment are more beneficial than those induced by radiation. © 2021 The Pathological Society of Great Britain and Ireland.